Systematic Literature Analysis for Supply Chain Conflicts: Paving the Way for Future Studies - Özcan, Seda; Sevil Oflaç, Bengü (International Journal of Contemporary Economics and Administrative Sciences, 2021)
This research provides a systematic overview regarding the Supply Chain Conflicts in Business-to-Business (B2B) relationships and defines and categorizes the main conflict areas and resolution mechanisms by conducting a content analysis. Based on the screening of 343 studies published mainly in the literature on marketing, business, management literature and other disciplines during 2010-2021, a systematic review and a content analysis were applied to find out the current situation and future research directions on this topic. In this research, within the context of descriptive analysis, sectoral-based analysis enables us to identify areas where conflicts are prevalent and where there is a need for further action. Regarding content analysis, highly fragmented synthesis presents how areas of conflicts and conflict resolution mechanisms are formed in the current B2B context. By providing a summary of the existing research direction on the subject, published in peer-reviewed international journals that publish research in English, this study contributes to the future academic work by identifying conflict sources and resolution methods to achieve better conflict management practices within the supply chains. With the findings of the research, companies can review their business practices and the underlying factors of conflict situations to improve their supply chains and gain ideas for their resolution. This research also contributes to the industrial marketing literature by providing an assembled and synthesized knowledge for scholars on supply chain conflicts with resolution mechanisms in both the social sciences and interdisciplinary management; deriving a comprehensive analysis of methods and insights addressed by researchers in the field.